Investigation of Ti1-xMoxCoSb Semiconducting Solid Solution - Stadnyk, Yu.; Romaka, V.; Нoryn A.; Romaka, L.; Krayovskyy, V.; Romaniv, I.; Rokomanuk, M. (Physics and Chemistry of Solid State, 2020)
The effect of doping of the TiCoSb compound (MgAgAs structure type) by Mo atoms on the features of the structural characteristics and behavior of the electrokinetic, energetic and magnetic properties of the Ti1-xMoxCoSb semiconducting solid solution (х = 0 - 0.06) in the temperature interval 80 - 400 K was studied. It was shown that including of Mo atoms (rМо= 0.140 nm) in the ToCoSb structure by substitution of Ti atoms (rТі= 0.146 нм) in 4a position is accompanied with non-monotonous variation of the lattice parameter values а(х), indicating unpredictable structural changes. Based on analysis of the variation of the electric resistivity values, thermopower coefficient, magnetic susceptibility and energetic characteristics, it was concluded that simultaneous generation in the crystal of the structural defects of the donor and acceptor nature (donor-acceptor pairs), which generate corresponding energy levels in the band gap of semiconductor and determine its electrical conductivity.